Manual Uterine Aspiration Simulation for Emergency Medicine Learners - Katherine Wegman; Caroline Gorka; Judith Linden; Shannon Bell; Stephanie N. Stapleton; Virginia Tancioco; Laura Welsh (Association of American Medical Colleges, 2024)
Introduction Manual uterine aspiration is a potentially lifesaving procedure for treating patients with hemorrhagic complications of early pregnancy loss. While early pregnancy loss is a common diagnosis seen in the emergency department, manual uterine aspiration education is lacking for emergency medicine physicians. Methods We designed a 90-minute procedural skills training session for 30 emergency medicine learners. The session included a brief lecture and video demonstration, followed by two micro-skills stations before finally completing the simulated procedure in its entirety. At each station, learners were asked to verbalize the steps and landmarks for the procedure before performing them on models. Participants completed a combined pre-post survey evaluating their perceived knowledge of the procedure and self-efficacy in performing the procedure. Results Thirty learners who participated in the workshop were surveyed, with a 100% response rate. All participants reported increased comfort with the procedure and knowledge about the procedure. All participants completed a successful simulated procedure. Participants also indicated increased interest in learning more about manual uterine aspiration and its potential application within the emergency medicine physician's scope of practice. Discussion We developed a workshop to train emergency medicine learners in manual uterine aspiration to stop life-threatening hemorrhage in the setting of early pregnancy loss. The workshop was well received by learners and increased their self-efficacy and desire for additional training with this procedure. Similar curricula should be tried at other institutions.